Genomic regions and pathways associated with thermotolerance in layer-type strain Taiwan indigenous chickens. (February 2020) - Zhuang, Zi-Xuan; Chen, Shuen-Ei; Chen, Chih-Feng; Lin, En-Chung; Huang, San-Yuan
Abstract: This study aimed to investigate genetic markers and candidate genes associated with thermotolerance in a layer-type strain Taiwan indigenous chickens exposed to acute heat stress. One hundred and ninety-two 30-week-old roosters were subjected to acute heat stress. Changes in body temperature (BT, ΔT ) were calculated by measuring the difference between the initial BT and the highest BT during heat stress and the results were categorized into dead, susceptible, tolerant, and intermediate groups depending on their survival and ΔT values at the end of the experiment. A genome-wide association study on survival and ΔT values was conducted using the Cochran–Armitage trend test and Fisher's exact test. Association analyses identified 80 significant SNPs being annotated to 23 candidate genes, 440 SNPs to 71 candidate genes, 64 SNPs to 25 candidate genes, and 378 SNPs to 78 candidate genes in the dead versus survivor, tolerant versus susceptible, intermediate versus tolerant, and intermediate versus susceptible groups, respectively. The annotated genes were associated with apoptosis, cellular stress responses, DNA repair, and metabolic oxidative stress. In conclusion, the identified SNPs of candidate genes provide insights into the potential mechanisms underlying physiological responses to acute heat stress in chickens. Highlights: Body temperature changes was significantly lower in heat-tolerant group. GWAS found SNPs associated with thermotolerance in chickens under acute heat stress. The candidate genes mainly associated with apoptosis, response to stress, etc.